Similarity solutions on mixed convection heat transfer from a horizontal surface saturated in a porous medium with internal heat generation - Ferdows, Mohammad; Liu, Don (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this work is to study the mixed convection boundary layer flow from a horizontal surface embedded in a porous medium with exponential decaying internal heat generation (IHG).
Keywords: mixed convection; horizontal porous surface; internal heat generation